M. Amin Abdullah dan Paradigma Integrasi–Interkoneksi: Rekonstruksi Epistemologi Keilmuan Islam dalam Menjawab Tantangan Era Kontemporer - Muhammad Ash Shabur; Wahyudin Halim; Ruslan R (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
This study aims to comprehensively examine the concept, philosophical foundations, implementation, and contemporary relevance of the integration–interconnection paradigm in the development of Islamic higher education and Islamic studies. Employing a qualitative library research method, this study adopts descriptive and philosophical approaches. Data were collected from M. Amin Abdullah's major works, scholarly books on Islamic epistemology, and reputable national (SINTA-indexed) and international (Scopus-indexed) journal articles relevant to the topic. The data were analyzed using content analysis and critical analysis to explore the theoretical foundations and practical implications of the paradigm. The findings reveal that the integration–interconnection paradigm seeks to establish a dialogical relationship among Islamic sciences, social sciences, humanities, natural sciences, and technology through multidisciplinary, interdisciplinary, and transdisciplinary approaches. The paradigm is grounded in three fundamental pillars: Hadlarah al-Nash (the civilization of religious texts), Hadlarah al-'Ilm (the civilization of scientific knowledge), and Hadlarah al-Falsafah (the civilization of philosophy and ethics), which complement one another in producing a more comprehensive understanding of Islam. Its implementation is reflected in curriculum development, academic research, and institutional transformation within Islamic higher education, particularly in the State Islamic Universities (UINs). Furthermore, the paradigm remains highly relevant in addressing the challenges posed by the Industrial Revolution 4.0, Society 5.0, artificial intelligence, social transformation, and other global humanitarian issues that require interdisciplinary collaboration.